CONCEPTUAL CONFUSION BETWEEN RELIGION AND PSYCHOLOGY AND ASSESSMENT ON THE REQUIREMENT FOR RELIGIOUS PSYCHOLOGY - Nuredin, Mensur; Kilic, Yusuf (International Scientific Journal Vision, 2022)
Emergence of several technologies and its relevant features have provided several organizations, state legislatives and normal human beings significant benefits in terms of enhancing their productivity and increasing their outcomes. Artificial Intelligence is one such technology that have sustained with beneficial parameters specifically for commercial firms Mikalef et al., (1). Artificial Intelligence incorporate features such as enhanced automation, smart intelligence services, accurate decision making and more. Nevertheless, the implementation of AI based features have significantly reduced the intervention of humans, Nahavandi (2), and the benefits it provides within health, environment, and economic sectors have raised several concerns. Potential misuse, unethical complexities, and biasness are some of the major hindrances which the technology faces. The states and national councils are accountable for mitigating such concerns and implement pertinent policies and regulations to extract out the positive aspects of Artificial Intelligence. Subsequent sections of this paper demonstrate and evaluates relevant information regarding Artificial Intelligence. Furthermore, other parts of this brief paper highlight the legal regulations associated with Artificial Intelligence. particular emphasis is placed on the regulatory parameters incorporated in Balkan States (Slovenia, Serbia, and North Macedonia) for Artificial Intelligence and Robots. Moreover, the regulations in American and European Law over these technologies are also discussed in this paper. Another important aspect which this paper covers is related to the determination of the capability which the robots possesses and discussion on how they can be accepted as legal subjects. Lastly, the paper ends with a conclusion and evaluation section based upon all the fundamentals briefed overall.